Toward a 2-Stage Theory of Emerging Market Multinationals - Grosse, Robert (Journal of Comparative International Management)

(untitled) (Management Futures, 2022)
I present a 2-stage theory in which emerging market firms first compete domestically based on traditional competitive advantages. Once they achieve a threshold stage, then they go overseas and are able to succeed based on company and industry characteristics, as well as emerging market characteristics. I expect to see that factors enabling firms to get to the threshold stage will include: brand value, low-cost production, experience/age, company size, possibly membership in a business group, and international sales (but not technology). Then I would expect that factors enabling firms to succeed internationally should depend on the industrial sector and the target market, as well as demonstrating emerging market idiosyncrasies such as ability to deal with high uncertainty in government policies and economic conditions as well as flexibility in dealing with business conditions. Most analyses of emerging market MNEs focus only on the last set of factors that are common to emerging markets.